THE INFLUENCE OF MULTIPROBIOTIC “APIBACT®» ON THE TBA-ACTIVE PRODUCTS LEVEL AND FUNCTIONING OF GLUTATHIONE LINK OF ANTIOXIDANT DEFENSE IN BLOOD SERUM OF RATS WITH LONG-TIME GASTRIC HYPOACIDITY - Pylypenko, S.V.; Korotkyi, O.G.; Gayda, L.M.; Beregova, T.V.; Ostapchenko, L.I. (World of Medicine and Biology, 2012)
Long-term decrease of gastric acid secretion by omeprazole leads to increase of TBA-active products level, activity of glutathione peroxidase, activity of glutathione transferase and to reduction of the level of reduced glutathione and glutathione reductase activity in blood serum of rats. Simultaneous introduction to the rats of omeprazole and multiprobiotic “Apibact®” reduce the activity of lipide peroxidation and has a modulatory effect on functioning of glutathione dependent system of antioxidant defense in rat blood serum as compared to administration of omeprazole alone.
Keywords: gastric hypoacidity; multiprobiotic «Аpibact®»; lipid peroxidation; antioxidant system